1997
DOI: 10.1103/physreve.55.7462
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous loss of ionization in argon-hydrogen plasma studied by fast flow glow discharge mass spectrometry

Abstract: Changes in ion abundance from the plasma of an abnormal dc glow discharge, using a copper cathode, have been studied as a function of ͑a͒ gas residence time in the discharge and ͑b͒ the amount of H 2 added to the positive column, without disturbing the discharge. The ArϩH 2 spectra show a severe, but selective, quenching of the ionization. All major ions are quenched except for Cu ϩ , which increases in abundance. It is shown that this cannot be explained by either ion-molecule reactions or the fast recombinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
50
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 37 publications
2
50
1
Order By: Relevance
“…Similar studies have demonstrated that Ar + H 2 spectra show a severe, but selective, quenching of the ionization. 108 In addition, a common trend with nitrogen and oxygen addition is the significant loss of the Ar and ArH ion signals. 109 Thus, it should be stated that the presence of reactive gases has to be seriously taken into account in the quantification process (e.g.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Similar studies have demonstrated that Ar + H 2 spectra show a severe, but selective, quenching of the ionization. 108 In addition, a common trend with nitrogen and oxygen addition is the significant loss of the Ar and ArH ion signals. 109 Thus, it should be stated that the presence of reactive gases has to be seriously taken into account in the quantification process (e.g.…”
mentioning
confidence: 99%
“…119 The use of a fast flowing glow discharge ion source allows high current, power, and sputtering rate, increasing the intensity of the analytes and their ratio to the water-derived ions. 108,120 Moreover, the analytical potential of modulated radiofrequency GD-TOFMS provides a unique ''multi-dimensional'' analysis tool, allowing simultaneous elemental and molecular quantification, with low sensitivity (<ppm) and high depth resolution (below 5 nm) in conductive and non-conductive thin layers, for most of the elements of the periodic table. Although some investigations have been previously conducted using a pulsed dc-GD coupled to a TOF mass analyzer, 121,122 it has been observed that pulsed dc-GD considerably fragments the molecules, reducing the efficiency to obtain molecular information.…”
mentioning
confidence: 99%
“…[53][54][55][56][57] Moreover, due to the low residence time of the different species in the plasma region, this configuration was denominated ''fast flow'' source. Additional theoretical modelling studies supported the hypothesis that improved transport efficiency is achieved using the fast flow Grimm-type GD source, resulting in enhanced sensitivity and reduced number of polyatomic species.…”
Section: Technical Backgroundmentioning
confidence: 99%
“…This is due to the rapid quenching of the excited states in the glow discharge, which produces a gradual decrease in the H intensities according to the increase in the Ar concentration in the mixture. Mason et al [20] performed the experimental studies of the anomalous loss of ionization in the Ar-H 2 plasma. Theoretically, using computer simulation, it has been studied by Bogaerts and Gijbels [19].…”
Section: B Optical Emission Spectrometry Measurementsmentioning
confidence: 99%